In-hospital mortality and morbidity of pediatric scoliosis surgery in Japan: Analysis using a national inpatient database. Issue 14 (April 2018) - Taniguchi, Yuki; Oichi, Takeshi; Ohya, Junichi; Chikuda, Hirotaka; Oshima, Yasushi; Matsubayashi, Yoshitaka; Matsui, Hiroki; Fushimi, Kiyohide; Tanaka, Sakae; Yasunaga, Hideo
Abstract : Abstract: Several previous reports have elucidated the mortality and incidence of complications after pediatric scoliosis surgery using nationwide databases. However, all of these studies were conducted in North America. Hence, this study aimed to identify the incidence and risk factors for in-hospital mortality and morbidity in pediatric scoliosis surgery, utilizing the Diagnosis Procedure Combination database, a national inpatient database in Japan. We retrospectively extracted data for patients aged less than 19 years who were admitted between 01 June 2010 and 31 March 2013 and underwent scoliosis surgery with fusion. The primary outcomes were in-hospital death and postoperative complications, including surgical site infection, ischemic heart disease, acute renal failure, pneumonia, stroke, disseminated intravascular coagulation, pulmonary embolism, and urinary tract infection. We identified 1, 703 eligible patients (346 males and 1, 357 females) with a mean age of 14.1 years. There were no deaths among the patients. At least one postoperative complication was found in 49 patients (2.9%). The most common complication was surgical site infection (1.4%). The multivariable logistic regression analysis showed that male sex (odds ratio, 2.22; 95% confidence interval, 1.28–3.70), comorbid diabetes (7.00; 1.56–31.51), and use of allogeneic blood transfusion (3.43; 1.86–6.41) were associated with the occurrence of postoperative complications. The present nationwide study elucidated the incidence and risk factors for in-hospital mortality and morbidity following surgery for pediatric scoliosis in an area other than North America. Diabetes was identified for the first time as a risk factor for postoperative complications in pediatric scoliosis surgery.